2007
DOI: 10.2478/s11658-006-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability in the RAD51 and BRCA1 regions in breast cancer

Abstract: Abbreviations used: AML -acute myeloid leukemia; BACH1 helicase -BRCA1 interacting protein C-terminal helicase 1 [Homo sapiens]; BRCA1 -breast cancer susceptibility gene 1; BRCT -BRCA C-terminus; LOH -loss of heterozygosity; RecA -RecA protein (Recombinase A); MRE11 -meiotic recombination 11 homologue A; NBS1 -Nijmegen breakage syndrome 1 (nibrin, NBN); p53 -tumor protein 53; RAD50 -RAD50 homologue (Saccharomyces cerevisiae) [ Abstract: Breast cancer is the most prevalent cancer type in women. Accumulating evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Rad51, a homolog of Escherichia coli RecA, is a DNA-dependent ATPase that binds cooperatively to single-stranded DNA to form a nucleoprotein filament that functions in the strandinvasion step of homologous recombination [39], which repairs chromosome damage and is indispensable for tumor suppression in humans. Recent studies have suggested that RAD51-associated protein 1 promotes homologous recombination and genomic stability by enhancing RAD51 recombinase [40]. XRCC3 is homologous to Rad51 and is essential for repairing double-strand DNA breaks by homologous recombination between sister chromatids [41].…”
Section: Discussionmentioning
confidence: 99%
“…Rad51, a homolog of Escherichia coli RecA, is a DNA-dependent ATPase that binds cooperatively to single-stranded DNA to form a nucleoprotein filament that functions in the strandinvasion step of homologous recombination [39], which repairs chromosome damage and is indispensable for tumor suppression in humans. Recent studies have suggested that RAD51-associated protein 1 promotes homologous recombination and genomic stability by enhancing RAD51 recombinase [40]. XRCC3 is homologous to Rad51 and is essential for repairing double-strand DNA breaks by homologous recombination between sister chromatids [41].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that curcumin-induced enhanced cisplatin sensitivity is mediated by suppression of the FA/BRCA pathway [ 167 ]. BRCA1 and RAD51 are two proteins leading to homologous recombination (HR) and thereby repair of double-strand DNA breaks [ 168 ].…”
Section: Polyphenols Modulate Cancer Drug Resistancementioning
confidence: 99%
“…In terms of somatic RAD51 mutations in tumor tissues, one study reported LOH of this gene -located on chromosome 15q14-15 -in 41 out of 127 BC patients (Gonzalez et al, 1999). Along this line, Nowacka-Zawisza et al evaluated LOH in RAD51 and its association with BC by analyzing the recombinase polymorphic markers D15S118, D15S214, and D15S1006 (Nowacka-Zawisza, Brys, Romanowicz-Makowska, Kulig, & Krajewska, 2007). Genomic deletion detected by allelic loss ranged from 29 to 46% of informative cases for the RAD51 region, 25% of the analyzed BCs displayed LOH for at least one RAD51 marker, and LOH in RAD51 appeared to correlate with the steroid receptor status, suggesting a role for enhanced risk in BC development.…”
Section: Breast Cancermentioning
confidence: 99%